Do Commonly Used Measures of Pain Intensity Only Reflect Pain Intensity in Youths With Bothersome Pain and a Physical Disability? - Miró, Jordi; de la Vega, Rocío; Gertz, Kevin J.; Thong, Ivan S. K.; Jensen, Mark P.; Engel, Joyce M. (Frontiers in Pediatrics, 2019)
The objective of this cross-sectional study was to evaluate the extent to which non-pain intensity factors influence the ratings of pain intensity on two commonly used measures: the Wong-Baker Faces pain rating scale (FACES) and the Verbal Rating Scale (VRS) in a sample of youths with physical disabilities and bothersome pain. Study participants came from a convenience sample of 115 youths (age:  = 14.4 years; SD = 3.3), who participated in a survey on the impact of pain in young people with a physical disability. They were administered measures of pain intensity, pain catastrophizing, depressive symptoms, pain interference and pain control beliefs. Zero-order correlation analyses were used to examine the associations among the pain intensity scores, while regression analyses were used to test the influence of the non-pain intensity factors on the pain intensity scores. Although pain intensity scores from all scales were significantly associated with one another, the correlations were moderate. Regression analyses showed that the FACES and VRS also reflect pain interference, in addition to pain intensity. The fact that the FACES and VRS ratings reflect more than pain intensity should be considered when selecting a pain measure. The results of this study also provide information to help interpret results after treatment.